Proizvodnja i evolucija kontejnera u svjetskim relacijama - Ivović, Jovo (Promet - Traffic&Transportation, 2012)
Transport technology of shipment and trans-shipment of freight by modern means and procedures and thus by means of containerization as a subsystem of integrated transport mode has over the past three decades exhibited an upward development trend. At an equal pace have proceeded manufacturing pl containers of different sizes, purpose and technology. Present annual production in the world has reached the figure of 500 000. Only in sea shipping industry of the world the existing capacities have reached the figure of 7 million t eu containers. Big containers, of 40 feet_ and over, are coming off the production line, while only a couple of years ago this could not have been reported. This has in turn its impact on the need for the introduction of modern port container handling cranes capable of lifting up to 600 kN (60 t) of load. Owing to an increased demand for containers in the world marketplace of transport services the leasing-oriented container manufacturing has been on the increase. Manufacturing of sophisticated container types has been under consideration to include chips for purposes of electronic monitoring of container flows in the transportation process.